Prep, push, pivot : essential career strategies for underrepresented women - Goredema, Octavia (Ascent Audio, 2022)
Advance your career with this insightful playbook for underrepresented women In Prep, Push, Pivot, award-winning career coach and author Octavia Goredema delivers an indispensable career coaching guide for women looking for a new job, dealing with job loss, pivoting to a new career, or returning to the workforce after an extended absence. You'll discover practical strategies you can implement at crucial times during your career, ensuring your considerable talents and skills are used to their full potential. In this important book, you'll: - Discover your true worth, cement your career values, and carve out a realistic and aspirational career plan - Learn how to position yourself for a promotion, navigate a break in your career, and integrate your role as a mother or caregiver with your professional life - Deal with monumental career changes, contribute to the development of the women around you, and benefit from an array of professional resources in your journey forward Perfect for women who are ready to overcome any obstacles that await them, Prep, Push, Pivot is a thoughtful road map to help women chart their professional and personal success.